Improving Sugarcane Bagasse as Animal Feed by Ammoniation and Followed by Fermentation with Trichoderma harzianum (In Vitro Study) - Samadi, Samadi; Wajizah, Siti; Usman, Yunasri; Riayatsyah, Denny; Firdausyi, Zidny Al (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2016)
Sugarcane bagasse is one of agro-industrial residues containing low nutrient content and difficult to be digested by animals. Â However, it can be recycled to produce value-added product such as protein-enriched animal feed by application feed technology such as ammoniation and fermentation. The purposes of these experiments were to evaluate the quality and in vitro digestibility of sugarcane bagasse by using two steps feed technology process: ammoniation and continued by fermentation process. Two studies were conducted in these experiments.Â The first study was to determine the quality of amoniated sugarcane bagasse after incubation at room temperature at different days (0, 7, 14, 21, 28 days) and the second study was to determine in vitro degestibility of Â ammoniated sugarcane bagasse fermented by using the various levels of sago flour (0%, 5%, 10% and 15% from sample total) and kept at room temperature for 21 day in an-aerobic condition. Parameters measured in this study were DM, CP, CF, pH, OM, IVDMD (in vitro dry matter digestibility), IVOMD (in vitro organic matter digestibility). The model used for the statistical analysis was completely randomized design (CRD). The results of the first study indicated that length of incubation was not significantly affect (P>0.05) on crude fiber content but had significant effect (P<0.05) on crude protein content but only for control treatment. For the second study concluded that administration of the various levels of sago flour into ammoniated sugarcane bagasse fermented with T.harzianum significantly influenced (P<0.05) on OM, IVDMD and IVOMD but had not significantly effect on pH value. The results of the study indicated that application 10% of soluble carbohydrate from sago flour was recommended for fermentation process based on the results of in vitro and fermented feed quality studies.